Insect molecular viology : advances and emerging trends - Bonning, Bryony C. (Caister Academic Press, 2019)
The volume opens with a description of the insect virome and the explosion in discovery of new viral taxa. The following four chapters focus on anti-viral immunity including endogenous viral elements some of which may provide the molecular basis for long-term anti-viral immunity, the discovery of new viral suppressors of RNA interference, the role of new classes of small RNA molecules in dictating infection outcomes, and the Drosophila-dicistrovirus model as a powerful resource for insect molecular virology. The application of omics tools to insect-vectored plant viral disease, recent advances.